Selected anti-health behaviors of junior high school students diagnosed with allergic disease - Bednarek, Anna; Emeryk, Andrzej; Matuszak, Joanna (Polish Journal of Public Health, 2012)
Introduction. A health risk behavior is characteristic of the period of adolescence, both in healthy adolescents as well as in those with a chronic disease, including allergy. It is associated with looking for their own identity and autonomy, as well as ways to cope with difficulties and stress. Aim. Identification of some anti-healthy behaviors of ju-nior high school students diagnosed with allergic disease. Material and methods. The study included a group of 100 junior high school students with diagnosed allergic disease in one of the public schools in Lublin, in 2008. The control group (100 persons) were adolescents from the same school, but without allergies. The research tool was authors’ questionnaire. For the comparison of both groups the statistical program SPSS 14.0 PL was used with the numbers, percentage calculations, and chi squared test of conformity and chi squared test of independence. Results. The attempts of smoking are confirmed by 38.3% of young people with allergy, and up to 61.3% of boys and 58.2% of girls in the control group. Pressure from peers when trying smoking was an important motivating factor to take these risky health behaviors in all patients with allergy, whereas in healthy young people it concerned 68.1% of boys and 78.0% girls. Similarly, alcohol consumption significantly more often was reported in the control group (87.2% in boys) than in adolescents with allergy (38.1% in girls). Conclusions. The pressure of peers has a significant impact on the occurrence of anti-health behavior in adolescents with allergic disease. Attempts to health risk behaviors in adolescents with allergies were more frequent in girls than in boys. Anti-health behavior strongly dominated in the control group, but its presence in adolescents with allergic disease may be a greater health risk than in the group of healthy adolescents.